Editors' Introduction: Policing the Protest Cycle of the 2010s - Maroto Calatayud, Manuel (Social justice, 2020)
An introduction to the journal is presented in which the editor discusses various articles published within the issue on topics like protest movements, the public safety law in Spain, and the mass mobilization in Hong Kong.